KNOWLEDGE AND ATTITUDE ASSOCIATED WITH SELF-MEDICATION AMONGST MEDICAL STUDENTS AT MEDICARE HEALTH PROFESSIONALS’ COLLEGE. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Awori , Sarah; Onyango, Richard (Student's Journal of Health Research Africa, 2024)
Background Self-medication is the consumption and use of medicinal products to treat disorders or symptoms of disease; it can also be the intermittent or continued use of a previously prescribed drug to treat recurring and chronic illness. Purpose To assess the knowledge and attitude of medical students towards self-medication in Medicare health professionals’ college Objective To determine the prevalence, assess the knowledge determine the attitude toward self-medication among medical students at Medicare health professionals’ college. Methodology A descriptive cross-sectional study was used which employed a quantitative method where data was collected once with no follow-up of respondents. This was a cheaper study design and it was done in a shorter period of time. Data was analysed using MS Excel package and descriptive statistics which include frequency and percentages were used and data was presented on figures, graphs, and tables. Findings The prevalence of self-medication was found to be high at 93% with the majority of respondent’s 32% practicing self-medication five times or more. 68.4% of the respondents had good knowledge of self-medication with 89% reporting having heard about self-medication before, almost all respondents 97.9% correctly defined Self-medication as consuming a drug without a prescription from a health worker, and 64.5% of respondents had good attitude towards self-medication with up to 43% believing that self-medication is not a dangerous practice,49.3 agreeing that SM is a part of self-care and 84% admitting they would recommend Self-medication to a colleague . Conclusion Despite their good knowledge about self-medication and its effects, the respondents had a positive attitude towards self-medication leading to them practicing it. This is evidenced by the high incidence rate of self-medication. Recommendation Sensitization of students on self-medication and its effects should be implemented by the institution to promote attitude change and increase knowledge among students.